Investigation on the Historical Origins of Traditional Chinese Medicine Diagnosis and Treatment of “Ruyong (Breast Abscess)” - Qi Liu; Ke Li; Yazhou Han; Mingru Wang; Xufeng Cheng (Chinese Medicine and Natural Products, 2025)
“Ruyong (breast abscess)” has a high incidence rate. Traditional Chinese medicine (TCM) diagnosis and treatment of this condition demonstrate significant advantages, including diverse therapeutic methods, outstanding efficacy, and high safety. Based on TCM theory and combining relevant ancient texts and modern research, this paper systematically summarizes the different understandings of “Ruyong (breast abscess)” by physicians throughout history in terms of disease names, etiology, pathogenesis, and treatment. The ancient names for Ruyong (breast abscess) were varied, also referred to as “Duru (stagnation in breast)” or “Naichuang (breast sore )”. Its symptoms are diverse, with the main clinical manifestations being localized redness, swelling, heat, pain, and poor milk discharge in the affected breast. The etiology is primarily attributed to “milk stasis” “liver qi stagnation and stomach heat” and “exposure to external pathogens”. Additionally, this paper summarizes the treatment experiences from ancient and modern medical texts and highlights the complementary effects of internal and external therapies. This study provides a reference for modern clinical understanding and treatment of “Ruyong (breast abscess)” in the hope of further improvement of clinical efficacy.